Lignin and Cellulose Nanofibers from Bambusa vulgaris Schrad (Bamboo): An Extraction, Preparation and Characterization Study - AbdulRasheed-Adeleke, Tawakaltu; Egwim, Evans Chidi; Ochigbo, Stephen Shaibu; Adefowope Saheed Alabi,; Christopher Chintua Enweremadu,; Okeniyi, Joshua Olusegun (Malaysian Journal of Science, 2025)
In this paper, lignin and cellulose nanofibers were extracted and prepared from Bambusa vulgaris schrad (B. vulgaris: bamboo) before being subjected to characterization investigations. These extractions and preparations of the lignin and cellulose nanofibers were carried out chemically using alkali combined with bleaching treatments together with acid hydrolysis and sonication. The cellulose nanofibers were then subjected to morphological and dimensional characterization of the Zetasizer, Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM) instruments. The functional groups investigation, using Fourier Transform infrared spectroscopy (FTIR), and thermal degradation via the Thermogravimetric analysis (TGA), of the bamboo lignin and of the cellulose nanofibers were also carried out. Results revealed that the percentage yields of the bamboo lignin and bamboo nanofiber were 21.91 wt% and 33.6 wt% respectively. The SEM and TEM investigations indicated the prepared nanofibers were rod-like in morphology, having sizes ranging from 20 to 100 nm. FTIR showed that the lignin extracted from bamboo typified G-S type lignin while the nanofibers are completely devoid of lignin. TGA revealed that the lignin was more thermally stable than the nanofiber under the test conditions. The obtained lignin and cellulose nanofibers showed promise for possible application as reinforcement agents in biodegradable nanocomposite film preparation.